A clarification of the taxonomy of Pleurothallis crocodiliceps (Pleurothallidinae, Orchidaceae) and four new species of Pleurothallis in subgenus Ancipitia - Wilson, Mark (Universidad de Costa Rica, 2017)
In this paper we summarize the taxonomic history of Pleurothallis crocodiliceps Rchb.f. and demonstrate that the species described by Reichenbach did not possess the stereotypical minute, pubescent, tri-lobed lip, with basal lobes modified into “horns”. The first two species described with such a lip were P. arietina and P. nelsonii. Rather than a single widely distributed, variable species, with a morphologically constant lip, P. crocodiliceps, we recognize the P. arietina-P. nelsonii species complex. Herein we describe four new species in this complex and discuss the morphological characters useful in distinguishing among the members of the complex. We also discuss the nature of the lip possessed by members of this complex and propose that it may mimic a female insect luring a male fly into pollinating the flower by pseudocopulation.